Theoretical study of phase behaviour of DLVO model for lysozyme and γ-crystalline aqueous electrolyte solutions - Melnyk, R. (Condensed Matter Physics, 2015)
Mean spherical approximation (MSA), second-order Barker-Henderson (BH) perturbation theory and thermodynamic perturbation theory (TPT) for associating fluids in combination with BH perturbation theory are applied to the study of the structural properties and phase behaviour of the Derjaguin-Landau-Verwey-Overbeek (DLVO) model of lysozyme and γ-cristalline aqueous electrolyte solutions. Predictions of the MSA for the structure factors are in good agreement with the corresponding computer simulation predictions. The agreement between theoretical results for the liquid-gas phase diagram and the corresponding results of the experiment and computer simulation is less satisfactory, with predictions of the combined BH-TPT approach being the most accurate. Середньосферичне наближення (ССН), теорiя збурень другого порядку Баркера-Гендерсона (БГ) i термодинамiчна теорiя збурень (ТТЗ) для асоцiативних рiдин в комбiнацiї з теорiєю збурень БГ застосованi
до вивчення структурних властивостей та фазової поведiнки моделi Дєрягiна-Ландау-Вервея-Овербека
(ДЛВО) водних розчинiв електролiтiв лiзоциму i гамма-кристалiну. Результати ССН для структурних факторiв добре узгоджуються з вiдповiдними комп’ютерними розрахунками. Узгодження мiж теоретичними
результатами для фазової дiаграми рiдина–газ i вiдповiдними експериментами та комп’ютерними симуляцiями є менш задовiльним. Кращого узгодження для фазових дiаграм дозволяє досягнути комбiнований БГ-ТТЗ пiдхiд.